The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/0022034512474668
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor and Cytokines Contribute to Extra-territorial Facial Pain

Abstract: The whisker pad area (WP) is innervated by the second branch of the trigeminal nerve and experiences allodynia and hyperalgesia following transection of the mental nerve (MN; the third branch of the trigeminal nerve). However, the mechanisms of this extra-territorial pain remain unclear. The ionotropic P2X(7) ATP receptor (P2X(7)) in microglia is known to potentiate, via cytokines, the perception of noxious stimuli, raising the possibility that P2X(7) and cytokines are involved in this extra-territorial pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In some inflammatory pain conditions without obvious morphologic changes, spinal microglia can still drive inflammatory pain by secreting the proinflammatory cytokine TNF-α. Microglia have also been shown to be involved with orofacial pain (Fan et al 2010; Ma et al 2015); activation of the P2X7 receptor in microglia of trigeminal nucleus facilitates extraterritorial facial pain via TNF-α secretion following transection of the mental nerve, the third branch of the trigeminal nerve (Murasaki et al 2013). Recent studies have found that the role of microglia in pain also depends on sex (Sorge et al 2015; Taves et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In some inflammatory pain conditions without obvious morphologic changes, spinal microglia can still drive inflammatory pain by secreting the proinflammatory cytokine TNF-α. Microglia have also been shown to be involved with orofacial pain (Fan et al 2010; Ma et al 2015); activation of the P2X7 receptor in microglia of trigeminal nucleus facilitates extraterritorial facial pain via TNF-α secretion following transection of the mental nerve, the third branch of the trigeminal nerve (Murasaki et al 2013). Recent studies have found that the role of microglia in pain also depends on sex (Sorge et al 2015; Taves et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the dorsal horn, microglialneuronal communication is initiated through activation of the purinergic receptor, P2X4 receptor, resulting in the release of brain-derived neurotrophic factor (BDNF) leading to activation of TrkB receptor and down-regulation of the neuronal potassium/chloride cotransporter KCC2 (Ulmann et al, 2008;Trang et al, 2009), or activation of the low affinity P2X7 receptor, resulting in the release of the lysosomal protease Cathepsin S (CatS) and CX 3 CL1 (Clark et al, 2010). Similar responses, including release of microglial TNF-α following activation of P2X7, can also occur in the TG following peripheral nerve damage (Ito et al, 2013;Murasaki et al, 2013).…”
Section: Inflammation and Neuronal Sensitizationmentioning
confidence: 99%
“…AMPA receptors, specifically the GluR2 and GluR3 subtypes have also been shown toincrease neural excitation within the nucleus caudalis and upper cervical spinal neuronsupon injury to the trigeminal nerve [69]. Purinergic receptor subtypes P2X3/7 have also been shown to facilitate both peripheral sensitization among trigeminal nerve afferents, and also central sensitization among neurons within the caudalis region of the VBSNC [56,[70][71][72]. Much like spinal neurons of the dorsal root ganglion, trigeminal ganglion neurons show expression of the transient receptor potential vanilloid 1 (TRPV1) following trigeminal nerve injury or experimentally applied capsaicin [73,74].…”
Section: Cellular Mechanisms Of Sensitizationmentioning
confidence: 99%
“…together enhance neuron excitability within the nucleus caudalis of the VBSNC [78,81,82]. During injury of the trigeminal nerve, microglia have also been shown to release proinflammatory cytokines such as IL-® andTNF, and chemokines such as CCL2, which contribute to central sensitization of neurons within the VBSNC, particularly following inflammation [71,[83][84][85]. Astroglia areanother type of glial cell that further maintain chronic orofacial pain.…”
Section: Glial Mechanisms Of Sensitizationmentioning
confidence: 99%